2017
DOI: 10.4067/s0717-97072017000200012
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Solid Phase Extraction for a New HPLC Method for the Determination of Gemifloxacin in Human Plasma and Breast Milk

Abstract: A simple analytical procedure, magnetic solid phase extraction combination to HPLC, has been developed for the analysis of gemifloxacin in human plasma and breast milk. Before chromatographic separation, magnetic solid phase extraction has been applied for sample preparation which is currently preffered extraction technique accordingly its simple, fast and efficient procedure. Fe 3 O 4 magnetic nanoparticles have been used as magnetic adsorbents, the adsorption process has been optimized. RP C18 column has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Electrochemical methods were also reported for the determination of quinolones [13,14]. The reported HPTLC methods included the determination of MX in tablets [15], MX with other fluoroquinolone antibiotics in industrial wastewater [16], LV with ornidazole or cefpodoxime [17,18] and GM [19,20]; the reported HPLC methods involved the determination of MX [21][22][23], LV [24,25], MX by stability studies [26], LV in urine [27], and GM in pharmaceutical and biological matrices [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical methods were also reported for the determination of quinolones [13,14]. The reported HPTLC methods included the determination of MX in tablets [15], MX with other fluoroquinolone antibiotics in industrial wastewater [16], LV with ornidazole or cefpodoxime [17,18] and GM [19,20]; the reported HPLC methods involved the determination of MX [21][22][23], LV [24,25], MX by stability studies [26], LV in urine [27], and GM in pharmaceutical and biological matrices [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%